School Principal Academic Supervision in Improving Teacher Performance at Cokroaminoto Kauditan Elementary School - Samsudin Hou (International Journal Labs, 2023)
This study aimed to delve into the management of Principal Academic Supervision and its impact on enhancing teacher performance at Cokroaminoto Kauditan Elementary School. The research employed a methodology involving observation and in-depth interviews with selected subjects. Data collection utilized a Likert scale through observation and questionnaires. The findings of the study underscored the significant influence of academic supervision by the principal on the professionalism of elementary school teachers in Purwakarta Regency. Examining the implementation of teaching supervision, the research highlighted challenges such as the time constraints faced by school principals, making the scheduling of supervision a complex task. Additionally, teacher behavior during supervision sessions varied considerably, indicating a dependence on the techniques employed by the school principal. Despite these challenges, the study revealed encouraging outcomes, with a majority of teachers surpassing the specified standard score criteria. The positive results suggest that the efforts invested in academic supervision have yielded favorable outcomes in terms of teacher performance. However, the study also emphasizes the need to address challenges in scheduling and teacher behavior to optimize the effectiveness of academic supervision in the future. Overall, the research provides valuable insights into the dynamics of academic supervision management and its role in elevating the professionalism of elementary school teachers.